Interactive Discussion Related to the Preparation of Pharmacy Professional Work Practice at the Health Center and Health Office - Saristiana, Yuneka; Prasetyawan, Fendy; Mildawati, Ratna; Marhenta, Yogi Bhakti; Kadir, Mujtahid Bin Abd; Arifin, Chandra; Rofiq, Abd; Astutik, Widhi; Rohmah, Eka Hayati (Mitra Jurnal Pengabdian Masyarakat Multidisiplin (MJPMM), 2025)
The Professional Pharmacy Practice Experience (PKPA) at Community Health Centers and Health Offices plays a crucial role in developing the professional competence of pharmacy students before they enter the actual workforce. To facilitate this preparation, an interactive discussion activity has been conducted as a means of training and collective reflection among students, supervising lecturers, and resource persons from the Health Office and community health centers. This discussion aims to enhance students' understanding of the roles and responsibilities of pharmacists within primary healthcare facilities (FKTP), while also identifying the challenges and solutions involved in the implementation of PKPA. The execution of the discussion demonstrated a high level of enthusiasm among students in exploring both the technical and non-technical aspects of the pharmacy profession, including the integration of clinical and managerial roles. The evaluation of the questionnaire reveals that over 85% of participants believe this activity significantly aids in preparing them to confront the PKPA with greater confidence. Group discussions highlight the significance of interpersonal communication skills, professional ethics, and teamwork collaboration as essential factors for the success of practice. A representative from the Health Department assessed that this activity is effective in aligning the perspectives between educational institutions and practical venues, thereby fostering ongoing synergy.